PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA PEMERINTAH DAERAH PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN BINTAN - Salihi Salihi; Ignasius Ridwan Hutauruk; Hasnarika (Bajang Institute, 2023)
The purpose of this research was to determine the effect of accountability and transparency on local government performance in the Regional Work Units (SKPD) of Bintan Regency. The method used in this research is quantitative associative method. Respondents in this study were sub-district employees in Bintan Regency as many as 39 people. Methods of data collection is done by using a questionnaire. The data analysis method used in this study is multiple linear regression using SPSS Ver.25. The conclusions obtained indicate that accountability and transparency affect the performance of local governments. The better the accountability and transparency implemented by Bintan Regency, the better the performance of the local government. The results of the discussion show that there is a partial and simultaneous influence between accountability and transparency on local government performance. This explains that accountability and transparency have succeeded in increasing the performance of local governments with a value of 41.6%.